Pelatihan Penanggulangan Kekerasan Terhadap Perempuan Di Kabupaten Nagan Raya - Anwar, Sufyan (LPPPM STAI Darul Hikmah Bangkalan, 2023)
Violence against women is considered a global public health problem. This is because the pattern of incidents of violence continues to increase every year, especially in Indonesia. There are a number of risk factors that are thought to be associated with the incidence of violence against women such as education level, beliefs and norms, antisocial personality, marital dissatisfaction, alcohol consumption and others. To reduce cases of violence against women which continues to increase, one of the efforts that can be done is through increasing knowledge to the community. The training on overcoming violence against women was held on August 19, 2021 for one and a half hours at the Village Community Empowerment Service Hall, Nagan Raya District. The activity was attended by 30 participants from various elements and carried out using the question and answer method after the presentation. Most of the participants showed good enthusiasm and spirit during the presentation and also during the discussion session, where many participants asked questions and shared their experiences about the violence that occurred in their environment. This indicates that there is an increase in participants' knowledge and understanding of violence against women. Participants who attend are expected to transmit their knowledge and understanding of violence against women to the wider community, especially to people in their work and living environments.